A cultural turn in New Testament studies? - Punt, J. (HTS teologiese studies, 2016)
This article considers intersections between cultural studies and New Testament studies. It ponders and focuses on possible approaches to the bearing of the ‘cultural turn’ on biblical studies. Following a brief consideration of cultural studies and its potential value for New Testament studies, four promising developments in cultural studies approaches to the New Testament are noted.Keywords: Cultural Studies; Postcolonial; Gender; Ideology; Autobiography